Crust and Upper Mantle Structure Beneath the Eastern United States. (22nd March 2022) - Chai, Chengping; Ammon, Charles J.; Maceira, Monica; Herrmann, Robert
Abstract: The Eastern United States (EUS) has a complex geological history and hosts several seismic active regions. We investigate the subsurface structure beneath the broader EUS. To produce reliable images of the subsurface, we simultaneously invert smoothed P‐wave receiver functions, Rayleigh‐wave phase and group velocity measurements, and Bouguer gravity observations for the 3D shear‐wave speed. Using surface‐wave observations (3–250 s) and spatially smoothed receiver functions, our velocity models are robust, reliable, and rich in detail. The shear‐wave velocity models fit all three types of observations well. The resulting velocity model for the eastern U.S. shows thinner crust beneath New England, the east coast, and the Mississippi Embayment (ME). A relatively thicker crust was found beneath the stable North America craton. A relatively slower upper mantle was imaged beneath New England, the east coast, and western ME. A comparison of crust thickness derived from our model against four recent published models shows first‐order consistency. A relatively small upper mantle low‐speed region correlates with a published P‐wave analysis that has associated the anomaly with a 75 Ma kimberlite volcanic site in Kentucky. We also explored the relationship between the subsurface structure and seismicity in the eastern U.S. We found that earthquakes often locate near regions with seismic velocity variations, but not universally. Not all regions of significant subsurface wave speed changes are loci of seismicity. A weak correlation between upper mantle shear velocity and earthquake focal mechanism has been observed. Plain Language Summary: The Eastern United States (EUS) experienced a complex series of geological activities. Earthquakes in the EUS have been recorded at several localized regions. A detailed subsurface structure can help us recover the geological history and studying earthquakes. We use multiple types of geophysical observations to reliably image the subsurface. Our images of the subsurface confirmed many findings from previous studies. The crust is thinner beneath New England, the east coast, and the southcentral United States. The interior of North America has a thicker crust. The upper mantle seismic speed is shower beneath New England, the east coast, and the western portion of the southcentral United States. A smaller region of slower upper mantle speed in Kentucky agrees with a published study, which linked the slower speed with a 75 Ma volcanic site. We compared images of subsurface against earthquake locations. Earthquakes often locate near regions with lateral subsurface structure changes. Lateral subsurface structure changes do not always collocate with earthquakes. The type (faulting) of earthquakes weakly correlates with the upper mantle seismic speed. Key Points: Inverting smoothed receiver functions, surface‐wave dispersion, and gravity for a 3D shear‐wave velocity model for the eastern US Our velocity model is broadly consistent with published results for the region Earthquakes often but not universally locate near areas with seismic speed variation, but not all velocity changes are loci of seismicity